TEACHING LEARNING PROCESS ON INTERPRETING CLASS AT ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA - SARI, YULIA PASCA ISPRI PARMATA (2011)
This study is to describe the teaching learning process on Interpreting class at English Department of Muhammadiyah University of Surakarta which covers the learning objective, the material, methods of teaching, evaluation and the strengthens and weaknesses of method in teaching interpreting. The data of this research are in the form of excerpts transcribed from the lecturer's attitude and interview in Interpreting class. The writer takes three interpreting lecturers who teach the sixth semester students at English Department 2008/2009 academic year of UMS are teacher X, teacher Y and teacher Z as the subject of the research. The writer uses descriptive qualitative especially ethnography research in analyzin g the data . The study shows that the learning objective of teaching interpreting consist of two objective, namely General Instructional Objective and Spesific Instructional Objective. The material used the lecturer not only comes from the textbooks which from the direction book but also news paper, magazines and the recordings. The methods of teaching divided into four types, such as Situational Language Teaching, Direct Method, Community Language Learning and Communicative Language Teaching. The evaluatio n system includes periodical test and final test In general, teaching interpreting appropriate the direction book but in application the lecturers doesn't maximum for using the method and media. They must inincrease their skills and be more creative in using various methods and media.